1989
DOI: 10.1073/pnas.86.23.9323
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of receptors for granulocyte colony-stimulating factor on human placenta and trophoblastic cells.

Abstract: Since radioiodination of human granulocyte colony-stimulating factor (G-CSF) is difficult, we synthesized a mutein of human G-CSF that retains full biological activity and receptor-binding capacity for at least 2 weeks after radioiodination. Receptors for human G-CSF were characterized in the plasma membrane fraction from the human term placenta (human placental membranes) and trophoblastic cells by using the III-labeled mutein of human G-CSF (KW-2228). The specific binding of III-labeled KW-2228 to placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(65 citation statements)
references
References 17 publications
2
62
1
Order By: Relevance
“…It should be pointed out, on the other hand, that G-CSF receptor expressions have been found on the surface of several nonhaematopoietic cell types, including human carcinoma cells (Bussolino et al, 1989;Uzumaki et al, 1989;Avaros et al, 1990). In fact, we previously reported that human transitional carcinoma cells expressing G-CSF receptor generated an acceleration of tumour cell proliferation (Ohigashi et al, 1992;Tachibana et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be pointed out, on the other hand, that G-CSF receptor expressions have been found on the surface of several nonhaematopoietic cell types, including human carcinoma cells (Bussolino et al, 1989;Uzumaki et al, 1989;Avaros et al, 1990). In fact, we previously reported that human transitional carcinoma cells expressing G-CSF receptor generated an acceleration of tumour cell proliferation (Ohigashi et al, 1992;Tachibana et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists concerning whether or not these G-CSF receptors are similar to the receptors expressed on cells of neutrophilic lineage, binding G-CSF with high affinity, and whether they are present on the surface of these non-haematopoietic cell types in sparse numbers (Bussolino et al, 1989;Uzumaki et al, 1989;Avaros et al, 1990). Moreover, at present, five different human G-CSF receptor isoforms or classes arising from alternative RNA splicing have been isolated, which are all identical in the extracellular domain but differ in their downstream sequences (Avalos et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The G-CSF has been found to beneficial effect on placental metabolism and trophoblast development. 17 Numerous cells involved in the reproductive physiological function, such as endothelium, fibroblasts, monocytes and endometrial cells produce G-CSF.…”
Section: Granulocyte Colony Stimulating Factor: the Moleculementioning
confidence: 99%
“…Regulates cell cycle activation, survival of the myeloid lineage, mediates the proliferation, differentiation and survival of neutrophil progenitors [52,57] Granulocyte-macrophage colony stimulating factor (GM-CSF)…”
Section: Growth Factorsmentioning
confidence: 99%